THE THEATRICALIZATION OF REALITY AND METATHEATRE OF NABOKOV-PLAYWRIGHT - Babenko, Olga Alexandrovna (Humanities Journal of University of Zakho, 2018)
The paper is devoted to the research of Vladimir Nabokov’s conception of theatricality in relation to drama as a literary form and stage performance. It presents the study of Nabokov’s understanding, artistic meaning and function of the conception, as well as the ways of its realization in all Nabokov’s plays. With regard to theatricality, the literary devices of the theatricalization of reality and ‘theatre within the theatre’, used by Nabokov for the purpose of emphasizing the content, expressing the author’s presence, and ironizing towards aesthetic and ethical phenomena, among others have been studied in the material of the plays The Tragedy of Mr. Morn, The Man from the USSR, The Event, and The Waltz Invention. These dramatic works include the whole range of attributes of the theatricalized reality and metatheatre: sporadically appearing scenes of an ‘internal’ play; duality of personages and performance of several roles by the same hero; heroes’ attempts to foretell the course of action, direct the play, and correct the ‘acting’ of another characters; personages using theatrical attributes and decorations.